1995
DOI: 10.1113/jphysiol.1995.sp020608
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor activation and the excitability of nerve terminals in the rat posterior pituitary.

Abstract: 1. The activation of GABAA receptors in nerve terminal membranes gates a Cl-channel.Experiments were conducted to determine how the activation of this receptor influences membrane potentials, action potentials and voltage-activated Na+ and K+ channels.2. When activation of the GABAA receptor produced only conductance changes and no voltage changes, action potentials changed only slightly. The threshold for action potential generation increased by 15%. GABA reduced the broadening of action potentials caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 33 publications
6
83
1
Order By: Relevance
“…Second, in paired recordings, small depolarizations of the calyx facilitated release, but depolarizations positive to Ϫ60 mV produced varied effects, sometimes causing inhibition (Awatramani et al, 2005). Facilitation is caused by the weak activation of voltage-gated Ca 2ϩ channels and the subsequent small basal Ca 2ϩ increase (Awatramani et al, 2005); larger depolarizations inhibit release by inactivating Na ϩ and possibly Ca 2ϩ channels (Graham and Redman, 1994;Zhang and Jackson, 1995); in some systems the shunting of the action potential by the Cl Ϫ conductance is the primary mechanism of inhibition (Cattaert and El Manira, 1999). In the calyx, K ϩ conductances limit slow depolarizations from reaching the Cl Ϫ reversal potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, in paired recordings, small depolarizations of the calyx facilitated release, but depolarizations positive to Ϫ60 mV produced varied effects, sometimes causing inhibition (Awatramani et al, 2005). Facilitation is caused by the weak activation of voltage-gated Ca 2ϩ channels and the subsequent small basal Ca 2ϩ increase (Awatramani et al, 2005); larger depolarizations inhibit release by inactivating Na ϩ and possibly Ca 2ϩ channels (Graham and Redman, 1994;Zhang and Jackson, 1995); in some systems the shunting of the action potential by the Cl Ϫ conductance is the primary mechanism of inhibition (Cattaert and El Manira, 1999). In the calyx, K ϩ conductances limit slow depolarizations from reaching the Cl Ϫ reversal potential.…”
Section: Discussionmentioning
confidence: 99%
“…The reverse argument is also true. (Zhang and Jackson, 1995) and retinal bipolar cell terminals (22 mM) (Billups and Attwell, 2002). Elevated [Cl Ϫ ] i is necessary for the depolarizing action of glycine or GABA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, tonic activation of presynaptic GABA A Rs modulates excitability of presynaptic terminals of the pituitary gland (Zhang and Jackson, 1995) and hippocampal mossy fibers (Ruiz et al, 2003). Other studies have shown that phasic changes in membrane potential at the calyx of Held spread back the axon, influencing AP generation up to 800 m away (Paradiso and Wu, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In such recordings, however, effects of subthreshold depolarizations may still have been inhibitory because of depolarization-induced Na ϩ current inactivation or K ϩ current activation (Zhang and Jackson, 1995;Monsivais et al, 2000;Lu and Trussell, 2001). To address this issue, we tested how GPSPs would alter the postsynaptic excitability after a delay of 30 msec.…”
Section: Subthreshold Excitatory Gpsps Enhance the Basket Cell Responmentioning
confidence: 99%
“…If the driving force E GABA -V m is negative, this hyperpolarizes the cell and inhibits its firing, except when hyperpolarization-induced excitatory conductances are activated, giving rise to rebound excitation [as in deep cerebellar nuclei (Llinas and Mühlethaler, 1988;Aizenman and Linden, 1999) or thalamic relay cells (Bal et al, 1995)]. Conversely, if the driving force is positive, the GPSP depolarizes the cell and is expected to increase its firing; however, the neuron can still be inhibited through shunting, as long as the GABA A conductances are active (Staley and Mody, 1992;Gao et al, 1998), or through longer-lasting, depolarization-induced Na ϩ channel inactivation (Zhang and Jackson, 1995) or K ϩ channel activation (Monsivais et al, 2000).…”
Section: Introductionmentioning
confidence: 99%